Implementation of Bhinneka Tunggal Ika Values in the Lives of the Bajo Ethnic Community: Strengthening Nationalism through Multicultural Education - Zulfaidil Zulfaidil (Journal of Sustainable Community Development, 2026)
Cultural, religious, and traditional diversity often has the potential to generate social friction if not properly managed. However, the Bajo community in Langara Laut Village has transformed this diversity into a source of harmony through the implementation of Bhinneka Tunggal Ika values. This study aims to explore the community’s understanding and application of diversity values, examine intergenerational differences in interpreting these values, and analyze the role of the Projek Penguatan Profil Pelajar Pancasila (P5) in sustaining these principles as a foundation for strengthening nationalism. This research employs a descriptive qualitative approach, utilizing observation, interviews, and documentation involving traditional leaders, teachers, and community members across different generations. The findings reveal that diversity values are internalized through mutual cooperation (gotong royong), interreligious tolerance, and cross-ethnic participation in traditional ceremonies. The older generation emphasizes the preservation of cultural traditions, while the younger generation demonstrates greater openness to globalization without abandoning their Bajo cultural identity. Furthermore, the P5 program has proven effective in enhancing the younger generation’s understanding by integrating local wisdom with national identity. Therefore, multicultural education grounded in local wisdom can serve as an effective strategy to foster nationalism and maintain unity within diversity.